Intentionally Retained Pressure‐Regulating Balloon in Artificial Urinary Sphincter Revision. (13th September 2012) - Köhler, Tobias S.; Benson, Aaron; Ost, Loren; Wilson, Steven K.; Brant, William O.
ABSTRACT Introduction. The traditional surgical approach for revision of a malfunctioning artificial urinary sphincter (AUS) includes removal and replacement of all device components, identical to that employed in the setting of an infected or eroded AUS. Aims. To describe outcomes of our technique in which we intentionally leave behind the original pressure‐regulating balloon (PRB) at time of AUS revision in a clinically non‐infected setting. Methods. We retrospectively reviewed our combined institutional series of 35 patients who underwent 36 AUS revisions in which the original pressure‐regulating balloon was left undisturbed. We removed and replaced the defective cuff and pump through a single peno‐scrotal incision for most patients requiring revision of a non‐infected AUS. The new PRB was then placed on the opposite side through this single incision. Main Outcome Measures. Assessment of outcomes, complication, and infection rate of this surgical series. Results. All of the patients had the original pressure‐regulating balloon placed through an inguinal counter‐incision. Mean follow‐up time was 14 months (2−33 months). Overall complication rate for the revision series was 11%. No infections or complications occurred secondary to the retained PRB. Conclusion. Follow‐up of our series provides evidence that retention of the original PRB at the time of non‐infected AUS revision is safe. Potential advantages include elimination of a counter incision and technically challenging exploration. By eliminating these aspects, the potentially resultant decreased operative time may help counter the theoretical yet unproven risk of infection from leaving the old PRB in place. Köhler TS, Benson A, Ost L, Wilson SK, and Brant WO. Intentionally retained pressure‐regulating balloon in artificial urinary sphincter revision. J Sex Med 2013;10:2566–2570.